The influence of social motivation diversity on group creativity: evidence from fNIRS hyperscanning - Liu, Ning; Ren, Sai Nan (Frontiers in Psychology, 2025)
Social motivation diversity, defined as the heterogeneity in group members’ preferences for maximizing either individual (pro-self) or collective (pro-social) outcomes, remains underexplored in its neural correlates with group creativity. This study employed functional near-infrared spectroscopy (fNIRS)-based hyperscanning to investigate interpersonal neural synchronization (IBS) during creative collaboration in 60 dyads (30 diverse, 30 homogeneous) of university students (N = 120), experimentally assigned based on social motivation. Each dyad completed both a creative task (umbrella design improvement) and a non-creative task (umbrella purchase plan). Results revealed that the diversity group showed significantly higher IBS increments in the prefrontal cortex (channels CH20 and CH23) compared to the non-diversity group. Furthermore, IBS in CH23 was positively correlated with novelty scores in the creative task. These findings suggest that social motivation diversity enhances group creativity through increased neural synchrony, supporting the notion that pro-self members contribute novel ideas while pro-social members facilitate integrative cooperation. This study provides novel neurophysiological evidence for the role of motivation-based diversity in collaborative creativity.